Microfibres and health: State of the evidence and research gaps - Taptiklis P; Boulic M; Phipps R; van Heerden H; Shaw C (Elsevier B V, 2025)
Microfibres are ubiquitous in the environment and there has been an increasing focus on health harms from them in recent decades. The current WHO guidelines defining health risks from microfibres focus on just the subset of microfibres that are inorganic and respirable. Recent studies have revealed large volumes of textile microfibres are present throughout the environment and that non-plastic microfibres are as common or more common than plastic microfibres. However, these are rarely included in the analysis of harms. This narrative review of textile microfibres sets out the state of our understanding of exposure to and harms from textile microfibres. We found that the epidemiological research reviewed here does not support the continued focus solely on the respiratory route of exposure nor only on plastic microfibres as hazardous to health. In fact, gastrointestinal as well as upper airway effects may also be increased by exposure to textile microfibres. Importantly, microfibres behave differently in the environment, and within the body in comparison to non-fibre particles, and therefore warrant separate investigation from particles and microplastics. The conclusion of this cross-disciplinary review is an urgent call for greater investigation of textile microfibres, separately from the also important issue of microplastics, and therefore, the inclusion of non-plastic fibre types in research going forward.
Keywords: Pollution; Hazardous exposure; Microfibres; Public health